Analisis dampak Bullying terhadap Psikologis Siswa di MTs Al-Uswah Kecamatan Kuala - Indah Sari, Suci; Sirait, Robin; Hemawati (LP2M STAI Darul Kamal NW Kembang Kerang NTB, 2024)
The school environment can affect the mental development and learning achievement of students. The good and bad conditions of the school environment will affect the development of students. Bullying behavior is one of the negative behaviors that often occurs in the school environment. Bullying is an aggressive action by someone to the target of bullying by attacking intentionally and without burden, done repeatedly because they consider the victim weak, easy to tease and unable to defend themselves. Bullying behavior has a serious impact on the mental development of students. Based on the results of the study, it can be concluded that the bullying behavior that occurs in students is mostly in the form of verbal bullying. The bullying treatment received by victims of bullying causes psychological disorders, victims of bullying experience lack of self-confidence and disorders in socializing